2010
DOI: 10.1242/jeb.051011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for color discrimination in the Atlantic sand fiddler crab, Uca pugilator

Abstract: SUMMARYFiddler crabs are intertidal brachyuran crabs that belong to the genus Uca. Approximately 97 different species have been identified, and several of these live sympatrically. Many have species-specific body color patterns that may act as signals for intra-and interspecific communication. To understand the behavioral and ecological role of this coloration we must know whether fiddler crabs have the physiological capacity to perceive color cues. Using a molecular approach, we identified the opsinencoding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 89 publications
5
30
0
Order By: Relevance
“…True color vision has been infrequently documented in crustaceans. Certainly, spectral sensitivity and the presence of different spectral classes of photoreceptors have been widely documented across crustacean species (Cronin and Forward, 1988;Frank and Widder, 1999;Rajkumar et al, 2010), but the behavioral evidence needed to confirm color vision (and discount confounding achromatic cues) is not common. Aside from tests in C. sapidus, color vision has been demonstrated in a fiddler crab, Uca mjoebergi, where females chose males with painted yellow claws over those with claws painted various shades of gray (Detto, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…True color vision has been infrequently documented in crustaceans. Certainly, spectral sensitivity and the presence of different spectral classes of photoreceptors have been widely documented across crustacean species (Cronin and Forward, 1988;Frank and Widder, 1999;Rajkumar et al, 2010), but the behavioral evidence needed to confirm color vision (and discount confounding achromatic cues) is not common. Aside from tests in C. sapidus, color vision has been demonstrated in a fiddler crab, Uca mjoebergi, where females chose males with painted yellow claws over those with claws painted various shades of gray (Detto, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, it has been envisaged that, on the basis of vertebrate studies, each photoreceptor cell expresses a single opsin gene, and multiple photoreceptor cells expressing several different opsin genes with different absorption spectra constitute a retina for color vision (30,31,33,34). However, recent studies have identified coexpression of multiple opsin genes in a single photoreceptor cell in compound eyes of butterflies and other arthropods (67)(68)(69)(70), raising the possibility that such opsin coexpression may enrich the photoreceptor diversity among invertebrates including dragonflies.…”
Section: Ecological Relevance Of Dorso-ventral Differentiation Of Opsmentioning
confidence: 99%
“…However, an expressed opsin does not necessarily have any functional significance in vision (for example, in the onycophoran Euperipatoides kanangrensis; Eriksson et al, 2013). Additionally, many crustaceans express more opsins than would be predicted based on photoreceptor physiology, as has been shown in stomatopods (Porter et al, 2013), brachyuran crabs (Rajkumar et al, 2010;Sakamoto et al, 1996), mysids (Frank et al, 2009), ostracods (Oakley and Huber, 2004) and branchipods (Kashiyama et al, 2009). Retinal transcriptomes, however, could be used to provide evidence for functional, expressed opsins.…”
Section: Limits Of This Studymentioning
confidence: 99%